Selection for seed yield in Andean intra-gene pool and Andean x middle American inter-gene pool populations of common bean - Singh, Shree P.; Terán Santofimio, Henry; Muñoz Perea, Carlos Germán; Osorno Gonzalez, JM (Springer, 2002)
Yields of large-seeded Andean (A) common bean (Phaseolus vulgaris L.) cultivars of Chile and Nueva Granada races are 40 to 60% lower compared to their Middle American (M) counterparts of small-seeded Mesoamerica and medium-seeded Durango races. Our objective was to use the concept of congruity backcrossing between Andean x Middle American inter-gene pool [AM 11833 = A 483 (A)///// A 686 (M) //// PVA 800A(A)/// Carioca (M)// Carioca (M)/ G 19833 (A)] and between races within Andean gene pool [i.e., intra-gene pool Andean, AA 11834 = A483 (A)//// Cardinal (A) /// Blanco Español (A) // BlancoEspañol (A) / Taylor (A)] to compare selection for seed yield improvement of large-seeded Andean beans. Seven hundred sixty seven F2-derived F3 (F2:3) families were produced for each population. Visual appraisal for total plant performance, combined with seed yield from non-replicated plots was used for selection of 551 families in F2:3, 182 families in F2:4, and 91 families in F2:5 in each population. Eight hundred twenty three F5:6 lines were developed from the 91 F2:5 families in each population. Visual selection, combined with seed yield in non-replicated plots was again used to select 294 lines in F5:6 in each population. Similarly, 44 highest yielding F5:7 lines were selected in AM 11833 and 39 F5:7 lines in AA 11834. Thus, single plant selections were made in the F2 and F5, and plants within each plot were harvested in bulk in F3, F4, F6, and F7. Thirty nine F5:8 lines from AA 11834 and 44 lines from AM 11833, parents, and checks were evaluated at Popayán and Quilichao, Colombia in 1998 and 1999. Selected lines in both populations, on average, out-yielded the mean of their large-seeded Andean parents. Mean yield of the lines selected from AM 11833 was 50% higher than AA 11834 lines. Twelve F5:8 lines out-yielded the highest yielding Andean parents G 19833 and A 483 in AM 11833, whereas only one line yielded significantly higher (p < 0.05) than the highest yielding parent A 483 in AA 11834. However, none of selected lines out-yielded small-seeded Middle American parents used in AM 11833 (A 686 and Carioca ). The mean 100 seed-weight of AA 11834 was 36 g compared to 28 G for AM 11833 F5:8 lines. Selected lines had similar days to maturity as parents in AM 11833, and matured 3 d later in AA11834. Correlation coefficients between yield and 100 seed-weight were negative in both populations. Yield and days to maturity were positively correlated in AA 11834.